Implications of Postponing the Distribution of Inheritance from an Islamic Legal Perspective - Tanjung, Aminah; Mariadi, Mariadi (Hukum Keluarga Islam IAIN LANGSA, 2023)
Conflicts between heirs and a reduction in the rights or shares that must be received as a result of some assets being controlled by one party generally result from delays in the community's inheritance distribution. To avoid this, it is crucial to comprehend and be aware of how inheritance is distributed in society from the standpoint of Islamic law. Qualitative research using a normative juridical perspective is the methodology employed. The distribution of inherited assets should not be delayed because the negative impact is greater than the positive impact felt by the community, so it is better for the community to immediately distribute the inherited assets after the heir dies and the costs of arranging the body, paying wills, and paying debts have been completed. The Compilation of Islamic Law (KHI) also specifies what needs to happen when heirs inherit money, as stated in Article 187, and what needs to happen when one family decides not to share the money, as stated in Article 188.